Relationships Between the Life Satisfaction, Meaning in Life, Hope and COVID-19 Fear for Turkish Adults During the COVID-19 Outbreak - Karataş, Zeynep; Uzun, Kıvanç; Tagay, Özlem (Frontiers in Psychology, 2021)
The current study investigated whether there are significant relationships between life satisfaction and meaning in life, hope and COVID-19 fear and the extent to which life satisfaction is predicted by these variables. The study group of this research consists of 1186 adults with the mean age of 41.04. Study group participants are consists of different cities of different regions of Turkey. As the data collection tools, the life satisfaction scale, the meaning in life scale, the dispositional hope scale and the COVID-19 fear scale were used. The results of the analyses have revealed that meaning in life, hope (actuating thinking and alternative ways thinking) are significant predictors of life satisfaction as positively. Besides, it is seen COVID -19 fear, age, gender and the presence of people infected with COVID -19 around aren't significant predictors of life satisfaction in adults.